7(y-6)=6y-16

Simple and best practice solution for 7(y-6)=6y-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(y-6)=6y-16 equation:


Simplifying
7(y + -6) = 6y + -16

Reorder the terms:
7(-6 + y) = 6y + -16
(-6 * 7 + y * 7) = 6y + -16
(-42 + 7y) = 6y + -16

Reorder the terms:
-42 + 7y = -16 + 6y

Solving
-42 + 7y = -16 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-42 + 7y + -6y = -16 + 6y + -6y

Combine like terms: 7y + -6y = 1y
-42 + 1y = -16 + 6y + -6y

Combine like terms: 6y + -6y = 0
-42 + 1y = -16 + 0
-42 + 1y = -16

Add '42' to each side of the equation.
-42 + 42 + 1y = -16 + 42

Combine like terms: -42 + 42 = 0
0 + 1y = -16 + 42
1y = -16 + 42

Combine like terms: -16 + 42 = 26
1y = 26

Divide each side by '1'.
y = 26

Simplifying
y = 26

See similar equations:

| 2a^2-3ab+b^2=0 | | -2(a+4)+8= | | 3+(2y+3)-4y=3 | | 180=3x+4x+40 | | ?x-2=1-2x | | .5/150= | | (9+8i)(7+i)=0 | | 25.6=8x | | p/6=9=14 | | C=0.7n+7.8 | | 10-2a=2a-6 | | 2=w/2.56 | | 5-7(10-10b)= | | an=2(1/4)^n-1 | | 15-(5m+8)=5+3m-14 | | 3x+5y=68 | | 4v/7=28 | | -5n+10=10-n | | 9(10x-9)-3= | | x+16y=202 | | x^2+1.8x-0.144=0 | | x+32+63=180 | | -4x+2(5k-6)=-3k-39 | | 7p+2(-1+7p)= | | 3(4x+2)-7x=10+3 | | 6+3*2-8-(6-4)= | | 180-48=x | | g-4=2 | | w^2+5w-104= | | -5(4t-3)+8t=6t-2 | | x+48=180 | | -12=-2k-3k |

Equations solver categories